Identification of microRNA profile specific to cancer stem-like cells directly isolated from human larynx cancer specimens. Issue 1 (December 2016) - Karatas, Omer; Suer, Ilknur; Yuceturk, Betul; Yilmaz, Mehmet; Oz, Buge; Guven, Gulgun; Cansiz, Harun; Creighton, Chad; Ittmann, Michael; Ozen, Mustafa
Abstract Background Emerging evidences proposed that microRNAs are associated with regulation of distinct physio-pathological processes including development of normal stem cells and carcinogenesis. In this study we aimed to investigate microRNA profile of cancer stem-like cells (CSLCs) isolated form freshly resected larynx cancer (LCa) tissue samples. Methods CD133 positive (CD133+ ) stem-like cells were isolated from freshly resected LCa tumor specimens. MicroRNA profile of 12 pair of CD133+ and CD133− cells was determined using microRNA microarray and differential expressions of selvected microRNAs were validated by quantitative real time PCR (qRT-PCR). Results MicroRNA profiling of CD133+ and CD133− LCa samples with microarray revealed that miR-26b, miR-203, miR-200c, and miR-363-3p were significantly downregulated and miR-1825 was upregulated in CD133+ larynx CSLCs. qRT-PCR analysis in a total of 25 CD133+ /CD133− sample pairs confirmed the altered expressions of these five microRNAs. Expressions of miR-26b, miR-200c, and miR-203 were significantly correlated with miR-363-3p, miR-203, and miR-363-3p expressions, respectively. Furthermore, in silico analysis revealed that these microRNAs target both cancer and stem-cell associated signaling pathways. Conclusions Our results showed that certain microRNAs in CD133+ cells could be used as cancer stem cell markers. Based on these results, we propose that this panel of microRNAs might carry crucial roles in LCa pathogenesis through regulating stem cell properties of tumor cells.